2006
DOI: 10.1200/jco.2006.06.0855
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Survival After Colorectal Cancer Diagnosis

Abstract: Recreational physical activity after the diagnosis of stages I to III colorectal cancer may reduce the risk of colorectal cancer-specific and overall mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
542
4
16

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 755 publications
(592 citation statements)
references
References 48 publications
30
542
4
16
Order By: Relevance
“…Majority of the women (65%) had low level of physical activity and reported lack of exercise. These observations are supported by numerous studies (Meyerhardt et al, 2006;Holick et al, 2008;Irwin, 2008;Wang and Chung, 2012).…”
Section: N=100) Impact Of Healthy Eating Practices and Physical Activsupporting
confidence: 72%
See 1 more Smart Citation
“…Majority of the women (65%) had low level of physical activity and reported lack of exercise. These observations are supported by numerous studies (Meyerhardt et al, 2006;Holick et al, 2008;Irwin, 2008;Wang and Chung, 2012).…”
Section: N=100) Impact Of Healthy Eating Practices and Physical Activsupporting
confidence: 72%
“…Physical activity among breast cancer survivors correlates with improved quality of life (Ogunleye and Holmes, 2009). Therefore, effective exercises improve not only the quality of life of cancer patients but also the prognosis for survival (Meyerhardt et al, 2006).…”
Section: Impact Of Healthy Eating Practices and Physical Activity Onmentioning
confidence: 99%
“…Simons et al (2013) concluded that regular long-term physical activity and fewer sedentary hours may protect against CRC. The benefit of physical activity on CRC exceeds the protective effect to improving the survival of patients; Meyerhardt et al (2006) suggested that physical activity after a CRC diagnosis might lower the risk of death from the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of relapse can be reduced through physical activity in colon cancer as well as in breast and prostate cancer [33,40,55].…”
mentioning
confidence: 99%